Campur Kode dan Identitas Digital: Praktik Stylization pada Akun TikTok @andreashabibiofficial - Fajrur Rohmaniyyah Alfaini; Mohammad Pribadi (Universitas Muhammadiyah Gorontalo, 2025)
This study analyzes the use of code-mixing and stylization as strategies for constructing digital identity on the TikTok account @andreashabibiofficial. The focus is on the consistent use of Arabic phrases such as habibyand yalla in short video content. Using a descriptive-qualitative approach, data were drawn from 7 selected videos posted between May 28 and June 11, 2025. The analysis reveals that code-mixing serves as a tool for personal branding and audience engagement, particularly among those who idealize Arab culture and a luxurious lifestyle associated with places like Dubai. These findings highlight the symbolic role of language practices in shaping digital persona on social media.